100 tahun Mohammad Natsir : berdamai dengan sejarah - Natsir, M., 1908-1993.; Hakiem, Lukman (Padang : Penerbit Republika, 2008)
Festschrift in honor of Mohammad Natsir, 1908-1993, an Indonesian nationalist figure, an Islamic leader, and the former Prime Minister of Indonesia, 1950-1951; collection of articles.
Includes bibliographical references.
Keywords: Natsir. M., -- 1908-1993.; Prime ministers -- Indonesia -- Biography; Indonesia -- Politics and government -- 20th century